Pemanfaatan Abu Vulkanik Sebagai Bahan Geostruktur Pada Perlindungan Tebing - , ilto abbas ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The eruption of Mount Merapi spewed millions of cubic yards of materials in the form of sand and light stones (bantak) as well as volcanic ash in very large quantities. Materials such as sand and light stones are spread evenly in the rivers with upper course in Mount Merapi. The volcanic ash of Mount Merapi contains 54.61% of SiO2, where silica content is a main element of cement formation, or in other words, the volcanic ash of Mount Merapi is pozolan in nature. The existence of these materials in any eruption is definitely going to be a serious problem for the environment, especially for those living around the slopes and rivers with upper course in Mount Merapi. Therefore, it is necessary to utilize the volcanic ash and light stones as materials in non-sand concrete mixture that can in turn be applied as materials in structure in a geo-engineering field. In this study, the volcanic ash was used as a substitute material of cement, while the light stone as the rough aggregate substitute in a mixture of non-sand concrete. The weight of volcanic ashes added as substitutes for cement were 0%, 25%, 30%, 35%, and 40% compared with the weight of cement. A comparison of cement and initial aggregate used was 1:5, the size of the light stones was 10-20 mm, and nila fas was 0.4. The testing of concrete was done to gain the mechanic attributes of concrete, i.e. the concrete pressure test and the flexure strength test of concrete block. The permeability test of concrete was done to find out the capacity of concrete in passing out water. Finally, the leaching test for severe metal content on concrete was done to find out the level of safety in surrounding environment. Results of the study show that the use of volcanic ash as the substitute of materials for cement in the non-sand concrete was able to reduce the use of the cement up to 75%. The resultant weight of concrete volume ranged from 2056 kg/m3- 2292 kg/m3, so it can be categorized as concrete with light structure. The concretes with variations of 0%, 30%, and 35% have the maximum of pressure strength at 28 days, and at 56 days the resultant compressive strength of concrete shows a less significant increase. At variations of 25% and 40%, the compressive strength of concrete at 56 days still show more increase compared with that when the concrete is still at 7 days toward 28 days old. The permeability test of stone fraction shows that the more the fraction formed from the structure of rock, the higher the value of permeability. The leaching test shows that heavy metal content in water was still under the determined threshold. The concrete with the content of volcanic ash for 35% can be used as materials in structure in a geo-engineering field. Results of the numerical analysis using Plaxis software version 8.6 to examine the safety factor of slope given the reinforcement by using gabion construction with the filling materials of volcanic ash in concrete block with a variation of 35% shown that the value of safety factor increases when the slope was given the reinforcement by using gabion construction. Keywords: volcanic ash, light stone, non-sand concrete, compressive strength, flexural strength, leaching, permeability.